1991
DOI: 10.1159/000153982
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Studies of Families Segregating the Silent Gene for Plasma Cholinesterase

Abstract: Seven families segregating apparently silent gene homozygotes have been investigated by enzyme-linked immunosorbent assays. These families confirm not only the heterogeneity of the silent gene in the form of E1S and E1t but in 3 families there is support for the segregation of the new gene E1x.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Cell-type specific Brd4 peaks match well with the enrichment of H4ac (Fig, 6 and Additional file 6 : Figure S5), showing the high affinity of Brd4 with H4ac. Brd4 overlapped with more than 20 % of pluripotent factors ( Oct4 , Sox2 , and Nanog ) and more than 30 % of c-Myc and n-Myc binding sites within 1Kbps [ 42 ]. However, the overlap with an insulator CTCF is only 6 percent.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-type specific Brd4 peaks match well with the enrichment of H4ac (Fig, 6 and Additional file 6 : Figure S5), showing the high affinity of Brd4 with H4ac. Brd4 overlapped with more than 20 % of pluripotent factors ( Oct4 , Sox2 , and Nanog ) and more than 30 % of c-Myc and n-Myc binding sites within 1Kbps [ 42 ]. However, the overlap with an insulator CTCF is only 6 percent.…”
Section: Resultsmentioning
confidence: 99%
“…24 Immunoassays have also been described which can determine enzyme concentration as opposed to activity. 25 Immunoassays, using antibody raised against usual enzyme, have been important in demonstrating the existence of types of`silent' variant, 26 but their use has been mainly con¢ned to the research arena because the clinical value of cholinesterase is associated with its activity rather than its concentration.…”
Section: Measurement Of Enzyme Activitymentioning
confidence: 99%
“…Whittaker et al [98] investigated seven families, all of which had isolated an apparent silent gene homozygote. Using enzyme-linked immunosorbent assays they confirmed that only one of the seven propositi could be truly classified as S/S.…”
Section: Inherited Variationsmentioning
confidence: 99%